Pro office 365 development - Collins, Mark J. (Apress, 2014)
Pro Office 365 Development, Second Edition, is a practical, hands-on guide to building applications for the cloud with Office 365. Combine Office 365 features out of the box with custom code to make the most of what this increasingly powerful and flexible platform has to offer. As an Office 365 developer, you have an amazing range of technologies at your fingertips. Build custom SharePoint apps in Visual Studio using HTML5, CSS, and jQuery. Create declarative workflow applications with Visio and SharePoint Designer. Use Access Web Database to publish your data on the web, or write Exchange and Lync applications. All these possibilities and more are covered. You also have unprecedented control and flexibility over how you use these technologies in your applications. With a powerful set of Office 365 APIs, you can now access and integrate Office 365 data directly into your web or native applications, with full control of authentication, authorization and discovery. No prior cloud experience is necessary. Sample projects are designed to bring the reader up-to-speed quickly, with full step-by-step instructions to maximize your success across the whole Office 365 suite. Whether you want to build desktop client applications or browser-only solutions, Pro Office 365 Development will show you how to do it.